Alcohol enhances type 1 interferon-α production and mortality in young mice infected with Mycobacterium tuberculosis. - Deepak Tripathi; Elwyn Welch; Satyanarayana Swamy Cheekatla; Rajesh Kumar Radhakrishnan; Sambasivan Venkatasubramanian; Padmaja Paidipally; Abhinav Van; Buka Samten; Kamakshi P Devalraju; Venkata Sanjeev Kumar Neela; Vijaya Lakshmi Valluri; Carol Mason; et al. (PLoS Pathogens, 2018)
In the current study, we used a mouse model and human blood samples to determine the effects of chronic alcohol consumption on immune responses during Mycobacterium tuberculosis (Mtb) infection. Alcohol increased the mortality of young mice but not old mice with Mtb infection. CD11b+Ly6G+ cells are the major source of IFN-α in the lungs of Mtb-infected alcohol-fed young mice, and IFN-α enhances macrophage necroptosis in the lungs. Treatment with an anti-IFNAR-1 antibody enhanced the survival of Mtb-infected alcohol-fed young mice. In response to Mtb, peripheral blood mononuclear cells (PBMCs) from alcoholic young healthy individuals with latent tuberculosis infection (LTBI) produced significantly higher amounts of IFN-α than those from non-alcoholic young healthy LTBI+ individuals and alcoholic and non-alcoholic old healthy LTBI+ individuals. Our study demonstrates that alcohol enhances IFN-α production by CD11b+Ly6G+ cells in the lungs of young Mtb-infected mice, which leads to macrophage necroptosis and increased mortality. Our findings also suggest that young alcoholic LTBI+ individuals have a higher risk of developing active TB infection.